Hypotension and heart rate variability after resistance exercise performed maximal and submaximal order - Victor Gonçalves Corrêa Neto; Claudio Melibeu Bentes; Geraldo de Albuquerque Maranhão Neto; Humberto Miranda (Desafio Singular, 2017)
The aim of the study was verified the blood pressure responses and the cardiac autonomic modulation after the strength exercise in two different conditions (maximal and submaximal). The subjects were divided in three groups, such as: maximal repetitions (age: 20.5 ± 0.6 years, weight: 63.7 ± 14.8, height: 1.7 ± 0.1, body mass index: 22.8 ± 4.5 Kilogram per square meter (kg/m²)), submaximal repetitions (age: 25 ± 4.1 years, weight: 69.1 ± 12.8, height: 1.8 ± 0.1, body mass index: 22.2 ± 1.7 (kg/m²))  and a control group (age: 23.7 ± 3.8 years, weight: 64.2 ± 15, height: 1.7 ± 0.1, body mass index: 21.8 ± 1.9 (kg/m²)). The blood pressure and the Heart Rate R-R intervals were measured before and during one hour after the session, with 10-minutes intervals length between measurements. The analyze of variance did not showed significant differences between experimental protocols to blood pressure (p > 0.05). However, the effect size was able to show that the most intense training caused a reduction in systolic blood pressure at times. Regarding cardiac autonomic response, the group that exercised the submaximal form exhibited a significant increase in LF / HF (p = 0.022) when 20 minutes' post-exercise. There was a not significant difference in cardiac autonomic modulation between protocols. The high intensity protocol has caused blood pressure reductions in more moments and it was over safer in relation to cardiac autonomic modulation, since it did not cause increased sympathetic activity during recovery.